Polydopamine surface-modified nanocarriers for improved anticancer activity: Current progress and future prospects - Sandip M. Honmane; Manoj S. Charde; Sachin S. Salunkhe; Prafulla B. Choudhari; Sopan N. Nangare (Elsevier, 2022)
From its inception, plenty of anticancer agents and gene therapies have been developed to account for cancer treatment. Despite this, the effectiveness of these therapies is flawed by toxic effects and failure to efficiently reach the target site. In this shade, novel drug delivery systems with advanced theranostic approaches have become a prerequisite in the domain of nanomedicines and nanotherapeutics. Despite this, the challenges associated with drug delivery have been urged to be discovered in the area of "drug delivery" intended for the delivery of drug to a targeted site for enhancement in clinical results. To deal with these issues, attachment of ligands that offer the selective targeting of active moiety in cancer therapy. In this present review, we have discussed the polydopamine (PDA) surface-modified nanocarriers for improved anticancer activity. In brief, methods for cancer treatment, challenges in cancer drug delivery, and approaches for targeted delivery of anticancer drugs have been described. Afterward, PDA in drug targeting and surface modification has been disclosed that including the significance and mechanism of PDA coating along with functionalization, toxicity, and cellular uptake of polymeric nanoparticles-polymerized dopamine (NPs-pD). Finally, the conclusion and prospects of PDA surface-modified nanocarriers have been discussed in detail. Importantly, the adaptability and flexibility of dopamine polymerization is playing a central role in functionalized nanoparticulate drug carriers in cancer treatment. Predominantly, multifunctionality present on the PDA surface and possible secondary modification approaches offer the potential for delivery of nanocarriers to target cancer cells very selectively and efficiently.